Current state of animal testing on cosmetic products in Indonesia, Malaysia and Singapore / Zulaila Aini Zulkifli and Idanawati Naharudin - Zulkifli, Zulaila Aini; Naharudin, Idanawati (Faculty of Pharmacy, 2023)
The rapidly expanding segment within the cosmetics and personal care industry represents a convergence of personal care and pharmaceutical sectors. Traditionally, animal testing has been utilized to ensure the safety and efficacy of cosmetic products for human use. However, in response to consumer demands, many prominent brands have transitioned to being cruelty-free, gaining widespread acceptance. The official members of the Association of Southeast Asian Nations (ASEAN), including Indonesia, Malaysia, and Singapore, have implemented the ASEAN Cosmetic Directive (ACD) as an agreement that aims to harmonize the regulations and standards for cosmetic products. However, the ACD does not provide specific legislation on animal testing. The directive defines cosmetics and specifies prohibited ingredients while allowing for permitted preservatives, UV filters, and colorants. This critical review focuses on the current state of animal testing for cosmetic products in Indonesia, Malaysia, and Singapore. The review was carried out with a reference to research works released between 2015 to 2022 by searching using an electronic database and involved referencing various articles. Its primary objective is to review the current state of animal testing on cosmetic products and the alternative methods used to ensure that cosmetic products are in regulatory compliance.